Determinants of Quantitative Optical Coherence Tomography Angiography Metrics in Patients with Diabetes - Tang, Fang Yao (Sci Rep, 2017)
Early microvascular damage in diabetes (e.g. capillary nonperfusion and ischemia) can now be assessed and quantified with optical coherence tomography-angiography (OCT-A). The morphology of vascular tissue is indeed affected by different factors; however, there is a paucity of data examining whether OCT-A metrics are influenced by ocular, systemic and demographic variables in subjects with diabetes. We conducted an observational cross-sectional study and included 434 eyes from 286 patients with diabetes. Foveal avascular zone (FAZ) area, FAZ circularity, total and parafoveal vessel density (VD), fractal dimension (FD), and vessel diameter index (VDI) from the superficial capillary plexus OCT-angiogram were measured by a customized automated image analysis program. We found that diabetic retinopathy (DR) severity was associated with increased FAZ area, decreased FAZ circularity, lower VD, lower FD, and increased VDI. Enlarged FAZ area was correlated with shorter axial length and thinner central subfield macular thickness. Decreased FAZ circularity was correlated with a reduction in visual function. Decreased VD was correlated with thinner macular ganglion-cell inner plexiform layer. Increased VDI was correlated with higher fasting glucose level. We concluded that the effects of ocular and systemic factors in diabetics should be taken into consideration when assessing microvascular alterations via OCT-A.